(untitled) (Research, Society and Development, 2020)
This article aims to report the experience of academic members of the university extension program entitled Heroes of the Smile that is part of the Dentistry course at the Federal University of Campina Grande (UFCG), during the performance of actions with infant patients and the impact of this in this context. The activities were developed with children and teenagers from 1 to 15 years old and their companions who attended the Noaldo Leite Children’s Hospital in the city of Patos - PB during the morning and afternoon shift during 2018. One of the objectives of the project was to minimize the impact the hospitalization process through playful activities, enabling a strategy for the child and its caregiver to face the hospital situation with less weight, promoting a reduction in the discomforts that affect the child. The work also provided volunteers and parents with the opportunity to experience aspects of the professional-patient-family relationship, enabling the development of sensitivity and personal growth in order to improve the quality of child care.